Exploring stakeholder experiences of interprofessional teamwork in sex development outpatient clinics. Issue 3 (4th May 2017) - Sanders, Caroline; Edwards, Zoe; Keegan, Kimberley
ABSTRACT: Adopting an interprofessional team approach to care of the child with rare conditions that can affect sex development (DSD) has been advocated by a consensus document within the last decade. In the United Kingdom, the approach appears orientated towards an interprofessional model with the integration of separate professions working in single consultations with families working collaboratively to focus on care using a person and family-centred lens. This concurrent mixed-methods UK study using questionnaires, observation, and interviews aimed to examine professionals', patients', and parents' expectations and interactions during DSD clinic. In adapting a model of patient and family-centred care, we were able to analyse the dimensions of care at the micro-, meso-, and macro-level. The micro captured the unique nature of the bio-psychosocial aspects of DSD, professional capabilities, and communication. The meso examined shared learning and objective setting as well as aspects of knowledge translation. The macro focused on the operational aspects and the emancipatory knowing embedded within DSD care. Complete data from participants ( n  = 105) were analysed from 47 outpatient clinical consultations and are reported as numerical data, tables, and participants' voices. Interestingly, all participants identified topics or concerns that were absent in the dialogues during consultation. Our findings informed the adaptation of a patient-focused model, thereby supporting the development of the concept of patient-centeredness, integration, and collaboration. This framework may serve as a platform, embedding existing evaluative tools and acknowledging the patient and professional partnership necessary in DSD care.